Influence of personal factors on ethical judgment of future accountants in Malaysia - Rasheed, Zuhudha (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2017)
Ethical conduct has been recognised as a pivotal element in the accounting profession, because it may encourage good conduct by accountants when making decisions. This research sought to identify the influence of personal factors on ethical judgement of future accountants in Malaysia. There are three research objectives for this study:(1) to investigate the influence of ethical ideology on ethical judgement of accounting students, (2) to investigate the influence of personal values on ethical judgement: and (3) to explore the influence of emotional intelligence on ethical judgement. The respondents of the study were undergraduate accounting students from three public universities, International Islamic University, Universiti of Kebangsaan Malaysia and the University of Malaya. A survey questionnaire comprised of instruments about ethical ideology, personal values, emotional intelligence and ethical judgment was distributed. A total of 205 responses were received and were redeemed as usable. In order to achieve the research objectives, a multiple regression was performed. The findings indicate that idealism, self-transcendence and social components are positive influences. On the contrary, the study discovered that relativism, self-enhancement, and personal components influence ethical judgment negatively. This study fills the research gap as research on personal factors on ethical judgement of future accountants is very few and scarce. In addition, it is expected that this study will initiate future research on the ethics of future accountants as well as provide a better understanding of the factors that can contribute to better ethical judgment by future accountants in Malaysia. It will give insight into the various parties on how to enhance ethical judgment among future accountants, which ultimately will improve the credibility of the accounting profession.